Sustainable Land Management for Mitigation of and Adaptation to Climate Change - World Bank (World Bank, Washington, DC, 2017)
The climate change (CC) caused by increase in atmospheric concentration of CO2 and other Greenhouse Gases (GHGs), can be addressed through adaptation and mitigation strategies. Adaptation consists of strategies which minimize vulnerability to CC. The objective is to increase resilience of the ecosystems and communities through adoption of specific sustainable land management (SLM) techniques that have adaptive benefits. On the other hand, the goal of mitigation strategies is to enhance soil and vegetation (land) sinks for absorbing atmospheric CO2 and to minimize net emissions. In the context of the resource-poor and small landholders of the developing countries, adaptation to CC is essential. Adaptation strategies are needed to enhance the positive and reduce the negative effects of CC. Adaptation is also needed because complete mitigation of CC may never occur. The strategy is to adopt those SLM technologies which have both adaptation and mitigation impacts at multiple scales (household, community, and watershed, national, global). There are four major areas in the tropics and sub-tropics where adoption of SLM technologies can help to both adapt to and mitigate CC: (i) tropical forest ecosystems (TFEs), (ii) tropical savannah and rangeland ecosystems (TSREs), (iii) world cropland soils, and (iv) salinized and degraded/desertified lands. Nonetheless, adoption of SLM technologies in the temperate regions (North America, Europe, Australia, Japan) is also important to adapting to CC. However, this report focuses on SLM options for developing countries of the tropics and sub-tropics.